Keterlibatan Masyarakat dalam Membangun Harmoni Sosial Muslim-Kristen Pra dan Pasca Konflik Etnik di Maluku - Nathalia Debby Makaruku; Izak Y. M. Lattu; Tony Robert C. Tampake (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2020)
The aim of the article is to give a sociological description and analysis toward the civic engagement of Taniwel Timur in building social harmony between Muslims and Christians, pre and post-conflict in Maluku. There are two main important points which are, the history of Muslims-Christians’ engagement in building a relationship and social interaction, and Muslims-Christians’ engagement becomes the basic in building harmonious social relationships. This research employed a qualitative research method through a structured interview technique with key informants, observation, and library study. The result of the research found that; first, the Muslims-Christians engagement divided into two which are the association form of civic engagement such as religious institutions, custom and government and everyday form of civic engagement consist of such simple, routine interactions of life as Christians and Muslims family visiting each other, eating together often enough, jointly participating in festivals and allowing their children to play together. Second, the Muslims-Christians’ engagement was based on strong brotherhood, cooperation with many parties, strong traditions and mutual trust. Association form and everyday form of civic engagement had the same position to build a strong social system. It also created a sphere of solidarity, justice, and fraternity. In conclusion, Taniwel Timur's society can construct a harmonious social life.